2018
DOI: 10.1177/2382120518771352
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in Internal Medicine Residents at Community-based Hospitals: A Cross-sectional Study

Abstract: Introduction:Many research reports revealed declining empathy in medical schools that continues in postgraduate years of training.Objective:The aim of this study is to examine the self-reported empathy levels of internal medicine (IM) residents in 3 community-based teaching hospitals.Methods:The Jefferson Scale of Physician Empathy, Health Professionals version, is an online, self-administered, questionnaire that was offered to 129 current and incoming residents at 1 osteopathic and 2 allopathic, IM training p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
5
5
0
Order By: Relevance
“…Although many studies reported declining self-assessed empathy at the clinical phase in undergraduate education [12,[22][23][24] as well as postgraduate residency [25,26], unchanged stable empathy was found in our study, which is consistent with very few previous studies [27]. Some studies reported that empathy of the resident, measured using the same JSE, was comparable to our results [28,29], and others reported increased results [27,30]. As mentioned in an earlier study [31], the timing of clinical training varies by country, as does the number of years it takes to graduate.…”
Section: Discussionsupporting
confidence: 89%
“…Although many studies reported declining self-assessed empathy at the clinical phase in undergraduate education [12,[22][23][24] as well as postgraduate residency [25,26], unchanged stable empathy was found in our study, which is consistent with very few previous studies [27]. Some studies reported that empathy of the resident, measured using the same JSE, was comparable to our results [28,29], and others reported increased results [27,30]. As mentioned in an earlier study [31], the timing of clinical training varies by country, as does the number of years it takes to graduate.…”
Section: Discussionsupporting
confidence: 89%
“…Although many studies reported declining self-assessed empathy at the clinical phase in both undergraduate education [12,[15][16][17] and during postgraduate residency [18,29], unchanged stable empathy was found in our study, which was consistent with very few previous studies [30]. Some studies reported that the resident's empathy score, measured using the same JSE, was comparable to our results [19,31], and others reported increased results [30,32]. As mentioned in an earlier study [33], the timing of clinical training varies by country, as does the number of years it takes to graduate.…”
Section: Discussionsupporting
confidence: 89%
“…Although many studies reported declining self-assessed empathy at the clinical phase in both undergraduate education [16,[19][20][21] and during postgraduate residency [22,33], unchanged stable empathy was found in our study, which was consistent with very few previous studies [34]. Some studies reported that the resident's empathy score, measured using the same JSE, was comparable to our results [23,35], and others reported increased results [34,36]. As mentioned in an earlier study [37], the timing of clinical training varies by country, as does the number of years it takes to graduate.…”
Section: Discussionsupporting
confidence: 89%